2018
DOI: 10.1021/acs.jpcc.8b05123
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interactions between Electron Donors and the Support in MgCl2-Supported Ziegler–Natta Catalysts

Abstract: Olefin polymerization using Ziegler–Natta catalysts (ZNCs) is an important industrial process. Despite this, fundamental insight into the inner working mechanisms of these catalysts remains scarce. Here, we focus on the low-γ nuclei 25Mg and 35Cl for an in-depth solid-state NMR and density functional theory (DFT) study of the catalyst’s MgCl2 support in binary adducts prepared by ball-milling. Besides the bare MgCl2 support and a MgCl2–TiCl4 adduct, samples containing donors that are part of the families of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…On the contrary, the static 35 Cl spectrum of frozen DES consists of a broad pattern with a breadth comparable to that of TEACl·H 2 O. Although the line shape is ill-defined, it does have several features, suggesting that there are several distinct chlorine sites in the frozen DES and that they have largely disordered local environment . It seems that although the TEA + ions are highly mobile in the frozen DES the mobility of the Cl – ions are significantly lower.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, the static 35 Cl spectrum of frozen DES consists of a broad pattern with a breadth comparable to that of TEACl·H 2 O. Although the line shape is ill-defined, it does have several features, suggesting that there are several distinct chlorine sites in the frozen DES and that they have largely disordered local environment . It seems that although the TEA + ions are highly mobile in the frozen DES the mobility of the Cl – ions are significantly lower.…”
Section: Resultsmentioning
confidence: 95%
“…Although the line shape is ill-defined, it does have several features, suggesting that there are several distinct chlorine sites in the frozen DES and that they have largely disordered local environment. 60 It seems that although the TEA + ions are highly mobile in the frozen DES the mobility of the Cl − ions are significantly lower. The discrepancy can be associated with the intrinsic differences in their roles in hydrogen bonding: The Cl − ions are expected to form hydrogen bonds with PE, whereas the TEA + ions are not.…”
Section: Resultsmentioning
confidence: 99%
“…Step 3: The material is activated with AlEt 3 , often in the presence of an external donor (e.g., alkoxysilane), and contacted with olefins. , It was shown that the highest stereo- and regioselectivity in polymerization reactions is achieved when either aromatic esters (e.g., ethyl benzoate, dibutyl phthalate) or 1,3-diethers (e.g., 1,3-dimethoxy-2,2-dialkylpropane) are used as IDs. , Moreover, it is generally accepted that the presence of IDs increases catalytic efficiency and directs polymerization toward formation of isotactic PP . Therefore, there has been significant effort devoted to studying the materials at the various steps of the catalyst preparation and in particular at step 2 focusing on the interaction of IDs with MgCl 2 supports, with the goal in particular to clarify the location of ID on the MgCl 2 surface with the intent to understand the origins of stereoselectivity of PP-ZNC. Therefore, in this study we focus on developing a methodology to enable the evaluation of the MgCl 2 –ID supports (Figure b), here using dynamic nuclear polarization surface-enhanced NMR spectroscopy (DNP-SENS) ( vide infra ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and computational studies show that IDs are likely bound to four- and five-coodinated Mg sites on catalytically relevant (110) and (104) facets of the MgCl 2 surface. This leads to the stabilization of primary MgCl 2 particles, which upon introduction of Ti directs formation of stereoselective sites. ,, However, little is experimentally known about the detailed interaction between the internal donor and the support even though it is likely very relevant for the understanding of the origins of stereoselectivity and further improvement of PP-ZNC.…”
Section: Introductionmentioning
confidence: 99%
“…MgCl 2 -supported Ziegler–Natta catalysts (ZNCs) dominate the ever-growing production of isotactic polypropylene, thanks to an exceedingly high stereoselectivity (isotacticity index I.I. > 98%) and a productivity in the order of several tons of polymer per gram of Ti. These systems consist of a solid precatalyst and a soluble cocatalyst: the former is typically obtained by reacting a MgCl 2 precursor with TiCl 4 in the presence of a first Lewis base (“internal donor”, ID), whereas the latter consists of AlEt 3 and a second Lewis base (“external donor”, ED). , Surface modification by the electron donors is essential for the stereoselectivity; decades of experimental and computational modeling studies demonstrated that ID and ED molecules, chemisorbed in the vicinity of the active Ti sites, shape the catalytic pocket similarly to the ancillary ligands of molecular catalysts.…”
Section: Introductionmentioning
confidence: 99%